One-step to prepare high-performance gas diffusion layer (GDL) with three different functional layers for proton exchange membrane fuel cells (PEMFCs). (19th July 2022) - Fu, Xuwei; Wen, Qinglin; Han, Jinli; Wei, Jun; Li, Yali; Ning, Fandi; Zhou, Xiaochun
Abstract: Gas diffusion layer (GDL) is one of the most important components of fuel cells. In order to improve the fuel cell performance, GDL has developed from single layer to dual layers, and then to multiple layers. However, dual or multi layers in GDL are usually prepared by layer-by-layer methods, which cost too much time, energy, and resources. In this work, we successfully developed a facile one-step method to prepare a GDL with three functional layers by utilizing the different sedimentation rates and filtration rates of short carbon fiber (CF) and carbon nanotube (CNT). The treatment temperature for this GDL is much lower than that of traditional method. The thickness of the GDL can be effectively controlled from as thin as 50 μm to more than 200 μm by simply adjusting the content of CF. The GDL with high flexibility is suitable to develop high performance flexible electronics. The fuel cell with the GDL has the maximum power density 1021 mW cm −2, which shows 19% improvement comparing to the conventional one. Therefore, this work breaks the traditional concept that GDL for fuel cells only can be prepared by very complex and high-cost procedure. Graphical abstract: Image 1 Highlights: One-step to prepare high-performance GDL with three functional layers. Contribution of CNT, short CF and PTFE to three functional layers carbon paper. Effects of CNT, short CF and PTFE in electric resistance, gas flux and porosity. Method to prepare GDL with multi-effects by precisely controlling the conditions.